A Study of Intention to Use of Halal Scanning Application Among Muslim Students at UTHM - IBRAHIM, SITI FATIMAH; HASIM, MUHAMMAD ASYRAF (Research in Management of Technology and Business, 2023)
Manipulation of Halal certification has been recurring for decades now; demanding a viable solution to effectively identify the authenticity of Halal products. Thus, this study aims to seek the intention to use of Halal scanning application among Muslim students of UTHM by adapting Technology Acceptance Model (TAM) to observe the influence of perceived usefulness and perceived ease of use on behavioral intention to use the application. The mediation effect of attitude toward use would also be tested. Quantitative research would be deployed by distributing questionnaires to the Muslim students of UTHM. According to Krejcie & Morgan (1970), a sample of 377 respondents should be observed in this study. Data analysis would be conducted through SmartPLS 3.0 and SPSS software. PLS-SEM method would be executed, which includes descriptive analysis, measurement model assessment, structural model assessment, and mediation analysis. The outcome of this study would contribute to the academic literature, the application developer, and other affiliated parties in discovering factors contributing to the adoption of the application in Malaysia as a tool to enhance market adoption of the application and ultimately leverage digitalization within the pre-packaged Halal food industry.